Potentially inappropriate medication use among community-residing elderly Canadians. - Turcotte, Katherine Elizabeth. (University of Ottawa (Canada), 1998)
This study is a two-part study of day-hospital patients and NPHS data. Objectives. To determine the prevalence of potentially inappropriate medication use among the elderly; to examine the relationships between selected variables and this outcome; to construct a model to identify higher risk individuals. Predetermined criteria were used to identify potentially inappropriate medication use. 11.1% ($\pm$10.3) of male and 23.1% ($\pm$10.2) of female day-hospital patients were classified with this outcome. Univariate LR identified five variables; multivariate LR identified five variables. 7.3% ($\pm$1.6) of Canadian elderly men and 7.1% ($\pm$1.3) of Canadian elderly women, taking at least one medication, were classified with this outcome. Univariate LR identified 14 variables; multiple LR identified five variables. Reducing the occurrence of potentially inappropriate medication use will lead to reduced drug-related morbidity, lower health care costs, and increased quality-of-life.
Keywords: Gerontology.